Giant atypical lipoma - Marta Regina Machado Mascarenhas; Lais de Abreu Mutti; João Marcos Goes de Paiva; Milvia Maria Simões e Silva Enokihara; Ival Peres Rosa; Mauro Yoshiaki Enokihara (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Liposarcomas correspond to the most common histological subtype of soft tissue sarcomas. They can be subdivided into: well differentiated or atypical lipoma, undifferentiated, myxoid, round, and pleomorphic cells. Atypical lipomas are the most prevalent and usually appear as asymptomatic softened tumors. They are locally aggressive but rarely lead to distant metastases. The diagnosis of this tumor is based on the imaging and histopathologic findings. Treatment consists of excision surgery with complete tumor removal. It has a good prognosis due to the low percentage of distant metastases. We report a rare case of giant atypical lipoma as well as the adopted therapy and evolution.